Avaliação dos efeitos farmacológico e toxicológico de 4- organocalcogeno-isoquinolinas - Sampaio, Tuane Bazanella (2014)
Monoamine oxidase (MAO) is a target enzyme in the treatment of several pathologies, being that new molecules which inhibit of a selective, potent and reversible manner their isoforms and without adverse effects are searched. In this way, the first manuscript of this dissertation evaluated the in vitro inhibitory potential of the 4-organochalcogen-isoquinolines on cerebral MAO-A and B activities, elucidating their kinetics profile and the interaction compound x enzyme. The results demonstrated that all compounds were selective inhibitors of MAO-B, being compound 3-phenyl-4-(selenophenyl) isoquinoline the most potent. The kinetics profile revealed a mixed and reversible inhibition of enzyme, consistent to the results of molecular docking. It is known that both organic selenium compounds and isoquinolines are linked to pro-oxidants situations, thus, it was investigated the in vitro effect of 4-organoseleno-isoquinolines on cerebral activities of the enzymes δ- aminolevulinate dehydratase (δ-ALA-D) e Na+, K+-ATPase, which have easily oxidized cysteine residues. Data demonstrated that compounds substituted with chloro, fluoro and trifluoromethyl in the aromatic ring bonded to the selenium atom of compound 3-phenyl-4-(selenophenyl) isoquinoline inhibited both sulfhydryl enzymes, which was not observed in the compound substituted with methyl and in a nonsubstituted compound. Furthermore, since the inhibition of enzymes δ-ALA-D and Na+, K+-ATPase was restored by dithiothreitol it is possible to propose the oxidation of cysteine residues by compounds. The selective and reversible inhibition of MAO-B and the low toxicological potential demonstrated by compound 3-phenyl-4- (selenophenyl) isoquinoline become this compound a candidate for more studies, which aim this enzyme as a therapeutic target.